2019
DOI: 10.1111/iej.13226
|View full text |Cite
|
Sign up to set email alerts
|

Altmetric analysis of the contemporary scientific literature in Endodontology

Abstract: Aim To analyse and visualize the knowledge structure of scientific articles in the field of Endodontology with high altmetric attention scores to discover hot topics, active researchers and the journals involved. Methodology On 5 June 2019, the altmetric database (Altmetric LLP, London, UK) was searched using the titles of 11 endodontic journals. Bibliometric data from endodontic articles and journals with an altmetric score >5 (top 5%) were retrieved from PubMed and analysed using the VOSviewer. Science mappi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 35 publications
2
21
0
1
Order By: Relevance
“…8 At the international level, several papers have applied bibliometrics in different areas of dentistry: oral surgery 9 , orthodontics, 10 paediatric dentistry, 11 periodontology, 12 endodontics. 13 Besides, a bibliometric study compared the characteristics of the scientific production on DPH between core journals and noncore journals. 2 The bibliometric analysis of DPH most-cited papers is a topic to be further explored.…”
Section: Introductionmentioning
confidence: 99%
“…8 At the international level, several papers have applied bibliometrics in different areas of dentistry: oral surgery 9 , orthodontics, 10 paediatric dentistry, 11 periodontology, 12 endodontics. 13 Besides, a bibliometric study compared the characteristics of the scientific production on DPH between core journals and noncore journals. 2 The bibliometric analysis of DPH most-cited papers is a topic to be further explored.…”
Section: Introductionmentioning
confidence: 99%
“…genomic medicine, nanotechnology and artificial intelligence, were not included among the hot topics. This finding may be explained by the retrospective nature of CSRs which was also reported in the field of Dentistry, [13,[35][36][37] Endodontology [38] and Iranian medical journals. [39] Citation analysis is considered an important part of scientometric research.…”
Section: Discussionmentioning
confidence: 74%
“…Also, several articles were not included in the present study since only the 25 most-cited articles were selected; 2 articles that have the same citation counts as the last ranked articles but with lower citation densities were not included [ 20 23 ]. Another important point is that authors, institutions and publishers may use self-mentions to stimulate the propagations of their own studies [ 59 ] and this is not taking into consideration in bibliometric counts. Despite is already known that this is a common practice among research groups and journals, several studies on this matter have shown that there is no need to exclude self-mentions in bibliometric analysis in Dentistry, as it does not appear to significantly influence the results and seems to be a healthy practice within the dental scientific community [ 60 61 ].…”
Section: Discussionmentioning
confidence: 99%